NMR evidence for oligosaccharide release from the dendritic‐cell specific intercellular adhesion molecule 3‐grabbing non‐integrin‐related (CLEC4M) carbohydrate recognition domain at low pH. (25th July 2014) - Probert, Fay; Mitchell, Daniel A.; Dixon, Ann M.
Abstract : Dendritic cell‐specific intercellular adhesion molecule 3‐grabbing non‐integrin‐related (DC‐SIGNR), also known as liver/lymph node‐specific intercellular adhesion molecule 3‐grabbing non‐integrin, CLEC4M, CD209L, and CD299, is a Ca 2+ ‐dependent lectin that has been implicated in increasing the infection rates of several viruses, including HIV, but the physiological role of DC‐SIGNR in healthy cells is currently not known with certainty. A close homologue of DC‐SIGNR, dendritic‐cell specific intercellular adhesion molecule 3‐grabbing non‐integrin, has been shown to act as a recycling endocytic receptor, which binds pathogens at the cell's surface and then releases them in the low pH environment of endosomal compartments. However, it is currently under debate in the literature as to whether DC‐SIGNR plays a similar role. In this work, we used NMR to explore whether the DC‐SIGNR carbohydrate recognition domain (CRD) shows any pH dependence in its ability to bind carbohydrates and Ca 2+ . We found clear evidence of reduced or abolished CRD‐binding affinities for three different glycans at low pH (4.2) as compared to neutral pH (6.8). We also report the assignment of the DC‐SIGNR CRD in the apo form, and use these new results to characterize the degree of structural rearrangement upon binding (or release) of Ca 2+ . Finally, we report a differential effect of pH on the affinities of glycans containing mannose exclusively versus glycans containing GlcNAc moieties. Our results lead us to propose that the DC‐SIGNR CRD rapidly and reversibly releases glycan ligands and Ca 2+ at reduced pH (behaviour that would be expected for an endocytic receptor), and that the binding of mannose‐containing oligosaccharides is more strongly affected by pH than the binding of GlcNAc‐containing oligosaccharides. Abstract : DC‐SIGNR (CLEC4M) is a potential recycling receptor on hepatic endothelia. Solution NMR demonstrates alternate binding affinities for different glycans at low and neutral pH, and shows structural rearrangements upon binding & release of Ca 2+ ions. DC‐SIGNR rapidly and reversibly releases glycan ligands and Ca 2+ ions at reduced pH, with oligomannose glycans showing greater pH sensitivity compared with GlcNAc‐containing glycans.